Characterisation of a CZT detector for dosimetry of molecular radiotherapy. (1st March 2017) - McAreavey, L.H.; Harkness-Brennan, L.J.; Colosimo, S.J.; Judson, D.S.; Boston, A.J.; Boston, H.C.; Nolan, P.J.; Flux, G.D.; Denis-Bacelar, A.M.; Harris, B.; Radley, I.; Carroll, M.
Abstract: A pixelated cadmium zinc telluride (CZT) detector has been characterised for the purpose of developing a quantitative single photon emission computed tomography (SPECT) system for dosimetry of molecular radiotherapy (MRT). This is the aim of the Dosimetric Imaging with CZT (DEPICT) project, which is a collaboration between the University of Liverpool, The Royal Marsden Hospital, The Royal Liverpool and Broadgreen University Hospital, and the commercial partner Kromek. CZT is a direct band gap semiconductor with superior energy resolution and stopping power compared to scintillator detectors used in current SPECT systems. The inherent detector properties have been investigated and operational parameters such as bias voltage and peaking time have been selected to optimise the performance of the system. Good energy resolution is required to discriminate γ -rays that are scattered as they are emitted from the body and within the collimator, and high photon throughput is essential due to the high activities of isotopes administered in MRT. The system has an average measured electronic noise of 3.31 keV full width at half maximum (FWHM), determined through the use of an internal pulser. The energy response of the system was measured across the energy region of interest 59.5 keV to 364.5 keV and found to be linear. The reverse bias voltage and peaking time producing the optimum FWHM and maximum photon throughput were 600 V and 0.5 μ s respectively. The average dead time of the system was measured as 4.84 μ s and charge sharing was quantified to be 0.71 % at 59.5 keV . A pixel sensitivity calibration map was created and planar images of the medical imaging isotopes 99 m Tc and 123 I were acquired by coupling the device to a prototype collimator, thereby demonstrating the suitability of the detector for the DEPICT project.